POLA KOMUNIKASI KEPEMIMPINAN KEPALA SEKOLAH PADA LEMBAGA PENDIDIKAN ISLAM UNTUK MENCIPTAKAN IKLIM KOMPETITIF DI SD ISLAM AL AZHAR 31 YOGYAKARTA - Rasmuin Rasmuin (ANDRAGOGI, 2019)
In the leadership of Islamic education, especially in the context of the school, a school principal is responsible for the progress and development of the school. The principal has a central role in the dynamics of the organization to determine the success of an educational institution. Al Azhar 31 Islamic Elementary School Yogyakarta is one of the basic Islamic education institutions in Yogyakarta. This institution has had a good reputation both at regional and national levels. This article seeks to uncover the role of school principals who have been able to bring this institution into a community favorite educational institution. From the field study, information was obtained that there were at least three important steps taken by the principal to bring the school to excellent and best performance, namely, 1) orbit the teacher or employee who "sinks" by continuing to motivate and give a trust to carry out certain tasks, 2) mapping the character of all the teachers and employees he leads, 3) Form a solid structural work partner and implement an open communication pattern.